Perbandingan pencapaian kognitif, afektif dan kompetensi pelajar Program Keusahawanan Remaja yang berlainan latar belakang keluarga - Othman, Norasmah; Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 2003)
A conducive environment may develop one's potential and ability to the needs of the society according to their respective fields. The environment refers to students' background. Studies have shown that one's background and beliefs (culture) affect the development of one's personality. Thus, the purpose of this research was to determine how student's background may influence their cognitive, affective and competency achievement in entrepreneurship. Samples were from the Adolescent Entrepreneurship Program. A questionnaire and a test were employed as the survey instrument in order to get student's achievement in cognitive, affective and competency. In addition a comparison of student's achievement in cognitive, affective and compentency were conducted in order to see their similarities and differences. The MANOVA technique was employed to gather this information. The results of this research indicated no significant different between types of paternal employment with student's achievement in general.